Improving Employee Performance in Business Process Outsourcing: The Role of Motivation and Competence in a Bandung Property Company - Asep Sazidin Wijaya; Nita Yura Roslina; Djadjun Djuhara; Adang Adang (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
With technological advancement, companies must adhere to digital progress in business rivalry. Enhancing human resources is a method to augment competitiveness. This study seeks to assess the impact of motivation and competence on employee performance inside a property company in Bandung. The employed methodology is descriptive and verification analysis involving 62 respondents, all employees. The analysis utilized correlation, path analysis, and the coefficient of determination (Kd) employing SPSS version 24, Microsoft Excel 2019, and Microsoft Word 2019. The study indicated that employee motivation, competence, and performance yielded favorable outcomes. A positive correlation exists between motivation and competence, with a coefficient of 0.400 and a % of determination of 82%. The direct influence of motivation on employee performance is 18%, but the influence of competence is 50%. The cumulative impact of motivation and competence is 68%, whereas 32% is affected by other variables.